Formação de professores para organizações não-governamentais - Ongs - Perez, Deivis (2009)
This thesis was turned for the analysis and reflection about the teachers training for the work at nongovernmental organizations (NGOs). The research problems that have presented were: What are the principal sources that direct the NGOs. What are the theories and the models of training and curriculum that direct the teacher s process of training made by a given NGO. Concerning the methodology, we made an option for a qualitative approach of research and, specifically for the realization of an instrumental study of case that has had as object the course Teachers Training for Nongovernmental Organizations prepared and offered by the trainer NGOs. The study of the course was made starting from the circumscription of two categories of references and data, named empirics, analytics or theorists. Starting from the data collected at camp, on the collective and individual semi-structured interviews and from the analysis of the course s documents, have emerged the empiric categories. The principal are: teachers training as a partnership among the participants of the process, the integrated curriculum, working for projects, reflexive model of training and broad curriculum. The analytic categories was identified starting from the bibliographic survey that was resulted the delimitation of the thesis theorist point about the modalities of education, highlighting the non-formal education made by the NGOs and the sociopolitical sources which direct the that organizations work, that are: the American approach of Third Sector, the critical approach of the Third sector, local social development, democracy, civil society and citizenship. Starting for the specific analysis of the case of the course Teachers Training for NGOs, we longed for, at the end of the work of research, present a joint of indications and suggestions that can be able to support the development of the other researches about the theme and, principally, offer information and systematized academic-scientific knowledge that can promote the development of courses or formative processes turned for teachers training to the work in NGOs, at the non-formal education line